Pengembangan E-Modul Praktikum Menggunakan Flip PDF Professional pada Materi Laju Reaksi Kelas XI IPA SMA N 1 Kec. Akabiluru - Dila Fitri; Dona Afriyani; Kuntum Khaira; Maya Sari (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2022)
This research is motivated by the absence of a special laboratory for chemistry subjects and the unavailability of a special practicum module, where teachers still use printed books as a practical guide and the lack of availability of tools and materials in the school laboratory. So that it has an impact on low chemistry learning outcomes. Based on this, the researchers conducted research on E-Module Development Using Flip PDF Professional on Class XI Reaction Rate Material. This study uses 4-D research (define, design, develop, and disseminate). The design in this study consists of only 3 stages, namely the definition stage which is carried out to find out how the conditions in schools are related to chemistry learning. This activity starts from interviews with teachers and students, analyzing the characteristics of students, analyzing practicum activities contained in textbooks, reviewing literature on e- modules and analyzing learning objectives. The design stage is used to design a practicum e- module using Flip PDF Professional on the reaction rate material. Develop stage, to see the validity and practicality of the practical e-module using Flip PDF Professional on the reaction rate material. The results showed that the validation of the practical e-module using Flip PDF Professional on the class XI reaction rate material that had been designed was very valid with an average percentage of 85.75% and the practicality results were very practical with an average percentage of 86.20%. With this it can be concluded that the practical e-module using Flip PDF Professional which has been designed is very valid and very practical to use.